2022
DOI: 10.3389/frsip.2021.812193
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose CT Denoising by ResNet With Fused Attention Modules and Integrated Loss Functions

Abstract: X-ray computed tomography (CT) is a non-invasive medical diagnostic tool that has raised public concerns due to the associated health risks of radiation dose to patients. Reducing the radiation dose leads to noise artifacts, making the low-dose CT images unreliable for diagnosis. Hence, low-dose CT (LDCT) image reconstruction techniques have offered a new research area. In this study, a deep neural network is proposed, specifically a residual network (ResNet) using dilated convolution, batch normalization, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Wang et al [29] found that some images with the same MSE value had obvious visual differences. In order to alleviate the problems caused by MSE, Marcos et al [30]introduced the perceptual loss into VGG-16 to compared the similarity between denoised CT and NDCT images in terms of high-level features. Yin et al [31]used the multi-perceptual loss to compare the feature differences from the VGG-19 network.…”
Section: Loss Functionmentioning
confidence: 99%
“…Wang et al [29] found that some images with the same MSE value had obvious visual differences. In order to alleviate the problems caused by MSE, Marcos et al [30]introduced the perceptual loss into VGG-16 to compared the similarity between denoised CT and NDCT images in terms of high-level features. Yin et al [31]used the multi-perceptual loss to compare the feature differences from the VGG-19 network.…”
Section: Loss Functionmentioning
confidence: 99%
“…Compared to traditional filtering methods, this approach achieves higher values of SSIM and PSNR. The study [15] suggests a Residual Network (ResNet) as a deep neural network architecture suitable for enhancing Low-Dose Computed Tomography (LDCT) images. There are many cutting-edge methods implemented in the network, such as dilated convolution, batch normalization, ReLU, and combined spatial and channel attention modules.…”
Section: Literature Surveymentioning
confidence: 99%
“…The below equation can be used to get the cutoff ๐œ‰ ๐ด๐‘‰๐ท๐ท๐น . [15] In the aforementioned equation, ๐œ‰ ๐ด๐‘‰๐ท๐ท๐น stands for the approximated variance, and _๐œ† ๐ด๐‘‰๐ท๐ท๐น is used to adjust the AVDDF filter's smoothing properties. The computation of the multivariate variance of the vectors within the window ๐‘Š is denoted by the term ๐œ“ ๐ด๐‘‰๐ท๐ท๐น , which is derived using below equation.…”
Section: ๐ด(๐‘ฅ ๐‘– ๐‘ฅmentioning
confidence: 99%